2020
DOI: 10.1136/postgradmedj-2020-138364
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of COVID-19 pandemic on postgraduate trainees: a cross-sectional survey

Abstract: BackgroundThe present study aimed to evaluate psychological impact of COVID-19 outbreak on postgraduate trainees in Pakistan by quantifying the symptoms of depression, anxiety and acute stress disorder and by analysing potential risk factors associated with these symptoms.MethodsFollowing Institutional Review Board approval, a cross-sectional study was conducted among 10,178 postgraduate trainees following COVID-19 outbreak through e-log system of College of Physicians and Surgeons of Pakistan. The nine-item P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 21 publications
4
73
0
3
Order By: Relevance
“…All 79 cross-sectional studies [41, 42, 44-50, 52-54, 56-63, 65-74, 77-122, 124-126] met four or more quality criteria, with 38 studies meeting all eight [41, 44, 48, 50, 54, 57, 59, 60, 63, 65-67, 74, 78-80, 83, 87-89, 91, 93, 96, 99-102, 104, 105, 107-109, 113, 119-121, 124, 126]. Most of the studies clearly defined criteria for inclusion in the sample, described study subjects and setting in detail, measured the exposure in a valid, reliable way, and used objective standard criteria for measurement of condition and appropriate statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All 79 cross-sectional studies [41, 42, 44-50, 52-54, 56-63, 65-74, 77-122, 124-126] met four or more quality criteria, with 38 studies meeting all eight [41, 44, 48, 50, 54, 57, 59, 60, 63, 65-67, 74, 78-80, 83, 87-89, 91, 93, 96, 99-102, 104, 105, 107-109, 113, 119-121, 124, 126]. Most of the studies clearly defined criteria for inclusion in the sample, described study subjects and setting in detail, measured the exposure in a valid, reliable way, and used objective standard criteria for measurement of condition and appropriate statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…More than two-thirds of the studies ( n = 60) [41-45, 47, 48, 50, 51, 53-55, 57, 59, 60, 62-68, 71, 72, 74, 75, 78-80, 83, 87-93, 99-105, 107-109, 111-117, 119-122, 124, 126] compared psychological and psychosomatic symptoms between frontline staff and other groups of participants (e.g., non-frontline healthcare providers, general public).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pooled prevalence of anxietyA total of 31 studies reported the prevalence of anxiety during COVID-19 in different samples from South Asian countries[46][47][48][49][50][51][52][53][54][55][56]58,59,[61][62][63][64][65][66]68,69,[71][72][73][74][75][76][77][78][79][80] . These studies used different scales to measureanxiety in respective samples, including the Generalized Anxiety Disorder 7-item (GAD-7) scale (n = 16), Depression, Anxiety and Stress Scale -21 Items (DASS-21) scales (n = 9), Hospital Anxiety and Depression Scale (HADS) (n = 4), Patient Health Questionnaire-4 (PHQ-4) (n = 1), and Self Reporting Questionnaire 20-items (SRQ-20) scale (n = 1).…”
mentioning
confidence: 99%
“…The prevalence of depressive symptoms, generalised anxiety disorder and acute stress disorder were significantly high in postgraduate trainees in this pandemic. 24 , 25 …”
Section: Covid-19 Pandemic and Cardiovascular Trainingmentioning
confidence: 99%